PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - AMIRULLAH -; RIATI - (STIE Indonesia Malang, 2022)
This study aims to determine and analyze the influence of motivation and organizational culture on employee performance. The method used in this study is a quantitative method and is carried out to answer three hypotheses. The instrument of this research is a list of direct questions that are distributed directly to the respondents. Respondents in this study were employees at the Sumbersekar Village Office, Dau District, Malang Regency as many as 34 people. The data analysis technique in this study used Multiple Regression Analysis.Based on the results of data analysis and discussions that have been carried out, that motivation has an effect on employee performance at the Sumbersekar Village Office, Dau District, Malang Regency. That organizational culture has an effect on employee performance at the Sumbersekar Village Office, Dau District, Malang Regency. That motivation and organizational culture simultaneously affect employee performance at the Sumbersekar Village Office, Dau District, Malang Regency. Keywords: Motivation, Organizational Culture, Employee Performance